Telltale diamagnetism at 50 K of a coordination polymer system. Issue 7 (3rd July 2022) - He, Jun; Ye, Xinhe; Liu, Zhiqing; Tang, Liangming; Hu, Jieying; Xu, Zhengtao
Abstract : The synthesis of coordination polymers (e.g. Prussian blue) is as old as modern chemistry itself, but never stops surprising people. We here report superconductivity observed of a designer coordination polymer system sporting the chemically soft mercaptan and hard carboxyl groups. The mercapto-carboxyl (dubbed Mercarb, or QiuSuo in Mandarin Pinyin) synergy hints at Daoism and here carries over from the molecular to the solid state: the soft sulfur donors bond with Co 2+ /Ni 2+ (or other transition metal ions) to afford 2D sheets for charge transport, while the interlayer metal-carboxylate domain is more ionic and mediates the transition into the superconductive state. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: A versatile open layered platform for potential superconductivity, this coordination polymer system is suited for doping: micropores for O2 oxidation, and μ2 -OH2 units to effect charge balance (by forming μ2 -OH − ).